Experimental observation of two massless Dirac-fermion gases in graphene-topological insulator heterostructure. (11th May 2016) - Bian, Guang; Chung, Ting-Fung; Chen, Chaoyu; Liu, Chang; Chang, Tay-Rong; Wu, Tailung; Belopolski, Ilya; Zheng, Hao; Xu, Su-Yang; Sanchez, Daniel S; Alidoust, Nasser; Pierce, Jonathan; et al.
Abstract: Graphene and topological insulators (TI) possess two-dimensional (2D) Dirac fermions with distinct physical properties. Integrating these two Dirac materials in a single device creates interesting opportunities for exploring new physics of interacting massless Dirac fermions. Here we report on a practical route to experimental fabrication of graphene–Sb2 Te3 heterostructure. The graphene–TI heterostructures are prepared by using a dry transfer of chemical-vapor-deposition grown graphene film. ARPES measurements confirm the coexistence of topological surface states of Sb2 Te3 and Dirac π bands of graphene, and identify the twist angle in the graphene–TI heterostructure. The results suggest a potential tunable electronic platform in which two different Dirac low-energy states dominate the transport behavior.